Hormone-control regions mediate steroid receptor–dependent genome organization - Le Dily, François; Vidal, Enrique; Cuartero, Yasmina; Quilez, Javier; Nacht, A. Silvina; Vicent, Guillermo P.; Carbonell-Caballero, José; Sharma, Priyanka; Villanueva-Cañas, José Luis; Ferrari, Roberto; De Llobet, Lara Isabel; Verde, Gaetano; et al.

(untitled) (Genome Research, 2018)
In breast cancer cells, some topologically associating domains (TADs) behave as hormonal gene regulation units, within which gene transcription is coordinately regulated in response to steroid hormones. Here we further describe that responsive TADs contain 20- to 100-kb-long clusters of intermingled estrogen receptor (ESR1) and progesterone receptor (PGR) binding sites, hereafter called hormone-control regions (HCRs). In T47D cells, we identified more than 200 HCRs, which are frequently bound by unliganded ESR1 and PGR. These HCRs establish steady long-distance inter-TAD interactions between them and organize characteristic looping structures with promoters in their TADs even in the absence of hormones in ESR1+-PGR+ cells. This organization is dependent on the expression of the receptors and is further dynamically modulated in response to steroid hormones. HCRs function as platforms that integrate different signals, resulting in some cases in opposite transcriptional responses to estrogens or progestins. Altogether, these results suggest that steroid hormone receptors act not only as hormone-regulated sequence-specific transcription factors but also as local and global genome organizers.